(untitled) (Actualizaciones en Sida e Infectología, 2023)
The emergence of SARS-COV-2 at the end of 2019 caused difficulties for the public health system to achieve the goals set by the WHO (World’s Health Organization) focused on the eradication of HIV, mainly in developing countries. With the purpose of evaluating the impact in our field, a public hospital in Ciudad Autónoma de Buenos Aires provided the information about the volunteers tested in the time span of January 2017 up until June 2022 according to the records from the main laboratory. The number of tests conducted during the pre-pandemic were double in comparison of the ones made during the pandemic. There were significant statistical differences in the average of monthly tests conducted, with a reduction of up to 60%. Even in the course of 2022, they stayed below the numbers before 2019. Regarding the prevalence of reactive serologies, they were similar to the ones from 2019 (2.4%). Considering the lack of verified diagnosis of HIV implies the progression to AIDS, vulnerability to opportunistic infections, exposure of other people to the infection, risk of life and perpetuation of the virus in the population, it is necessary to actively retake the fight against HIV.